вирішити приклад

вирішити приклад

  • У першому випадку множимо на поєднане:
    = Frac {4 (2 sqrt {2})} {(4-2)} - 5 + 2 sqrt {2} = frac {4 (2 sqrt {2})} {2} -5 + 2 sqrt { 2} = 2 (2 sqrt {2}) -5 + 2 sqrt {2}=
    =4-2 sqrt {2} -5 + 2 sqrt {2} = 4-5 = -1
  • Рішення у вкладенні.
  • вирішити приклад

    Понравилась статья? Поделись с друзьями:
    Добавить комментарий

    ;-) :| :x :twisted: :smile: :shock: :sad: :roll: :razz: :oops: :o :mrgreen: :lol: :idea: :grin: :evil: :cry: :cool: :arrow: :???: :?: :!:

    + 78 = 88